Selecting the key research areas in nano-technology field using technology cluster analysis: A case study based on National R&D Programs in South Korea - Lee, Yong-Gil; Song, Yong-Il (ELSEVIER, 2007)
In the early 21st century, Korean government issued a policy recommendation that Korean public research institutes should select strategic research fields to concentrate their resources, based on a careful review of the various strategic R&D factors. The government has emphasized the "selection and concentration" strategy for the efficient use of R&D resources and as a way to increase the national competitiveness of Korea. This paper suggests a method, a "Technology Cluster Analysis," for selecting the strategic research areas, mainly targeting large, multi-disciplinary and long-term programs. The technology cluster analysis groups near technologies together based on key indicators. In this study, the method is applied to national R&D programs in the nano-technology field. Fifty-six nano-technologies are analyzed and grouped into three main clusters based on the survey data from 180 experts. Technological distances and correlations among individual technologies are depicted by hierarchical dendrogram. Three main clusters in nano-technology field are found and termed nano-materials, nano-devices, and nano-bio. These three clusters are expected to be the core technology clusters in nano-technology field in South Korea. (C) 2006 Elsevier Ltd. All rights reserved.